(untitled) (Western European Journal of Medicine and Medical Science, 2026)
In the era of globalization and rapid technological advancement, intercultural communication has become a central component of modern education systems. The increasing mobility of people, ideas, and information has made it essential for individuals to develop the ability to interact effectively across cultural boundaries. This article examines intercultural communication as an object of the educational system, exploring its theoretical foundations, pedagogical significance, and practical implementation. The study highlights the importance of integrating intercultural competence into curricula to prepare students for global citizenship. Furthermore, it analyzes teaching strategies, challenges, and the role of educators in fostering intercultural awareness. The findings suggest that education systems must adopt innovative and inclusive approaches to ensure effective intercultural learning outcomes